2007
DOI: 10.1530/eje.1.02331
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone treatment increases plasma levels of adiponectin and decreases levels of resistin in overweight women with PCOS: a randomized placebo-controlled study

Abstract: Objective: Abdominal obesity, insulin resistance and compensatory hyperinsulinaemia play a central role in the pathogenesis of the polycystic ovary syndrome (PCOS). Abdominal adipose tissue is a source of adipokines, such as adiponectin and resistin, both of which may be involved in the development of insulin resistance and chronic inflammation in PCOS. Ghrelin, an important regulatory peptide of food intake, may also play a role in metabolic disturbances related to PCOS.The aim of this study was to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 61 publications
5
43
2
1
Order By: Relevance
“…Similarly, a trial involving 70 patients without diabetes but with the metabolic syndrome found that adiponectin levels were significantly increased by 164% (p < 0.001) after 8 weeks of treatment with rosiglitazone, compared with placebo [68]. Four months of treatment with rosiglitazone also significantly increased plasma levels of adiponectin when compared with placebo (p < 0.001) in a study of 30 overweight/obese women with polycystic ovary syndrome [59].…”
Section: Adiponectinmentioning
confidence: 94%
“…Similarly, a trial involving 70 patients without diabetes but with the metabolic syndrome found that adiponectin levels were significantly increased by 164% (p < 0.001) after 8 weeks of treatment with rosiglitazone, compared with placebo [68]. Four months of treatment with rosiglitazone also significantly increased plasma levels of adiponectin when compared with placebo (p < 0.001) in a study of 30 overweight/obese women with polycystic ovary syndrome [59].…”
Section: Adiponectinmentioning
confidence: 94%
“…The clinical correlates of levels of adipokines are corroborated by the finding that the circulating levels of resistin in humans are lowered by treatment with the anti-diabetic insulin-sensitizing PPARG agonist drugs rosiglitazone and pioglitazone, while such treatment concomitantly increases the levels of adiponectin (15)(16)(17).…”
Section: Introductionmentioning
confidence: 89%
“…Instead, the resistin gene polymorphism is associated with BMI in women with PCOS, suggesting that resistin might be related to adiposity in PCOS (Xita et al 2004). In addition, in a randomized placebo-controlled study, treatment with the insulin sensitizer rosiglitazone significantly reduced serum resistin levels in overweight women with PCOS, implying the contribution of resistin to insulin sensitivity improvement during treatment (Majuri et al 2007). In summary, resistin seems to be an important adipokine that is involved in obesity, IR, and PCOS.…”
Section: Resistinmentioning
confidence: 98%